(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In the article, the impact of mining enterprises on the environment, including the closure of enterprises, has led to an acute environmental situation. The increased technogenic impact on the environment has led to a tense environmental situation in the vicinity of mining enterprises, including closed ones. Recently, the concept of “accumulated environmental damage” has entered environmental practice. To a large extent, characteristic of the study area, considered as the negative consequences of the impact of mining waste on the ecosphere, caused by environmental pollution, loss and depletion of natural resources, destruction of ecosystems, creating a real threat to human health, flora and fauna, as well as material values. Physico-mechanical soil disturbance and chemical pollution of ecosystems in general, including surface and groundwater, led to the degradation of natural systems and the emergence of environmentally-related diseases in the population of the mining village. The practical significance of the results of mining operations lies in the creation of a favorable living environment for the population of the village after mining, environmental safety of storing toxic waste, and the rational use of natural resources at mining enterprises. The problem of detecting and eliminating the consequences of environmental damage accumulated in past years has been on the agenda in Kyrgyzstan and other countries for a long time.